From Jerusalem to Rome: The Geographical Aspect of Magic [Dari Yerusalem ke Roma: Aspek Geografis dari Sihir] - Han, Chandra (Diligentia: Journal of Theology and Christian Education, 2022)
Just as magic was undermined in the Acts of the Apostles, its spread throughout the whole region of the Greco-Roman Region was also undermined. Although the magic episode occurred six times in the Acts of the Apostles, the demonstration of the geographical aspect of magic in the Acts of the Apostles was undermined. The prominent question regarding the presence of magic in the Greco-Roman reigns is how serious was magic during the Greco-Roman Era for Christianity so that the gospel could be proclaimed to the end of the world? This article will demonstrate the seriousness of magic to impede the spread of the gospel is obvious when analyzing the geographical spread of magic. The aim of this article is to demonstrate the magical context of each Roman city where magic was there. Moreover, this article also demonstrates the significance of the geographical aspect of magic for the spread of the Gospel. This geographical aspect will be argued within the context of the apologetic purpose of the Acts of the Apostles and the spread of the gospel to the end of the world to fulfill Jesus’ command to his disciples. This research will employ a literature method. The analysis will analyze the city of Samaria, the island of Cyprus, the strategic city of Ephesus, Philippi, and Malta. Application regarding the proclamation of the gospel for our contemporary world will be provided in the section of discussion and result before the conclusion.